The Effect of Nurses' Caring Behavior on Patients' Family Anxiety in Intensive Care Unit (ICU) Room - Nola Yohana Sitanggang; Mestiana Br. Karo (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
Background: Anxiety is frequently experienced by family members of patients admitted to intensive care units (ICUs), largely due to uncertainty regarding the patient’s condition and dependence on specialized treatment. Nurses’ caring behavior is often regarded as an essential component of supportive care that may help reduce this anxiety. This study examines the association between nurses’ caring behavior and the anxiety levels of patients’ families in the ICU setting. Methods: A non-experimental research used cross sectional design was employed using purposive sampling. The study involved 30 family members of ICU patients. Data were collected using a validated caring behavior questionnaire and the Hamilton Anxiety Rating Scale (HARS). The Spearman rank correlation test was used for statistical analysis. Results: The findings showed a p-value of 0.505 (> 0.05), indicating that nurses’ caring behavior was not significantly associated with the anxiety levels of family members. Conclusion: Nurses’ caring behavior did not demonstrate a significant impact on family anxiety in the ICU. Nevertheless, caring practices remain an essential component of holistic nursing care, and their consistent implementation is recommended to support families during critical illness.